Synthesis and thermal, optical and morphological characterization of oligomeric polyamides based on thiophene and alkyl/phenyl‐silane moieties. Study of the electrospun deposition process. Issue 29 (15th April 2016) - Jessop, Ignacio A.; Tundidor‐Camba, Alain; Terraza, Claudio A.; González‐Henríquez, Carmen M.; Tagle, Luis H.
ABSTRACT: Polyamides were synthesized from a thiophene‐containing diamine by direct polycondensation with organosilane acyl dichlorides. The obtained polymers had good solubility in common organic solvents and THF, with TDT10% values upper than 400 °C and T g between 150 and 180 °C. Combination of these properties reveals that the processability of the polymers was increased with respect to traditional aromatic polyamides. Inherent viscosity values and SEC analysis indicated low molecular weight species. Samples showed high visible transparency and bandgap values associated to insulating materials. Polymer solutions were deposited using electrospun technique and their surface properties were studied by SEM. Spheres were created according to electric field applied during deposition process. Low molecular weight and conductivity prevent charge accumulation in the surface hindering fibers generation. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43702. Abstract :